2015
DOI: 10.1111/eth.12406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Female‐Female Aggression in a Sexual/Unisexual Species Complex

Abstract: The maintenance of sexual reproduction is still a largely unresolved question in evolutionary biology, and one of the most puzzling aspects of this is the coexistence of sexual and asexual females. This often leads to widespread niche overlap, posing an interesting challenge to competitive exclusion theory. In this study, we investigate how the aggressive behaviors between females in a sexual/unisexual mating complex of mollies (Poecilia latipinna and P. formosa) differ, and the effects these behaviors have on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
(117 reference statements)
0
23
2
Order By: Relevance
“…The presence of clonal recognition in an asexual vertebrate is interesting in itself, but a key question is: what adaptive benefit might Amazon mollies derive from kin recognition? Due to intraspecific competition and the extensive niche overlap between Amazons and their sexual hosts, we hypothesized that females may show more aggression towards non-sisters (and heterospecific sexual females) than clonal sisters to acquire access to limited resources, like food and potential mates [ 24 , 49 50 ]. Indeed, aggression in Amazon mollies has been shown to decrease their overall fitness via lower body fat condition and increasing energy expenditure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of clonal recognition in an asexual vertebrate is interesting in itself, but a key question is: what adaptive benefit might Amazon mollies derive from kin recognition? Due to intraspecific competition and the extensive niche overlap between Amazons and their sexual hosts, we hypothesized that females may show more aggression towards non-sisters (and heterospecific sexual females) than clonal sisters to acquire access to limited resources, like food and potential mates [ 24 , 49 50 ]. Indeed, aggression in Amazon mollies has been shown to decrease their overall fitness via lower body fat condition and increasing energy expenditure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has already shown that P. formosa is more aggressive when compared to the parental species, and this aggression increases over time. (Makowicz & Schlupp, 2015) suggest that since in natural conditions, groups are very plastic with high group turnover, individuals might have low tolerance for consistent interactions with the same individuals. Furthermore, due to the fact that these fish require sperm from males of one of the parental species (Bierbach et al, 2011; Ingo Schlupp, Parzefall, & Schartl, 1991), Amazon mollies might be more aggressive to out-compete heterospecific females for access to males.…”
Section: Discussionmentioning
confidence: 99%
“…This parthenogenic Poeciliid species provides a unique opportunity to generate genetically identical 'replicate individuals' controlling for any intrinsic genetic differences and allowing us to pinpoint the effects of early social experience on later adult behaviour. These mollies are found in large shoals in the wild [14] and are known to exhibit considerable femalefemale aggression, making repeated dominance interactions likely in this species [15]. Our experimental design manipulated an individual's success at early dominance interactions by placing it in a (i) winning, (ii) losing or (iii) alternating winning and losing role for the first two months of life (prior to sexual maturity).…”
Section: Introductionmentioning
confidence: 99%